Urban Games to Design the Augmented City - De Luca, Vanessa; Bertolo, Maresa (Eludamos: Journal for Computer Game Culture, 2012)
Seen through the eyes of games, urban environments can appear as museums, storytelling venues, or intense multi-user experiences that could attract people away from their living rooms into the city. Engaging physical, social, and emotional levels, urban games emerge today as powerful resources, able to lead to a playful reading of the augmented city we live in. Observing recent play practices such as hybrid treasure hunts and geo-location games, several “patterns” can be noticed and recognized as new models for negotiating the density of urban landscapes in a physically and digitally mixed reality. Discovering and wandering across cities are dynamic patterns that invite the research and design community to consider the importance of retrieving the human ludic attitude to explore spaces; these can be recognized in “Rhabdomancy” and “Flânerie”, two interesting methods to design the augmented city. They perpetuate a constantly renewed playful relationship between places and human activities, offering to players - as modern citizens - an opportunity for actively participating in contemporary city-life.